Perioperative Safety and Outcomes of SGLT2 Inhibitors in Diabetic Kidney Disease Patients Undergoing Non-Cardiac Surgery: A Meta-Analysis of Euglycemic Ketoacidosis and Acute Kidney Injury Risks - Rizki Jaya Amal; Abdullah; Maimun Syukri; Desi Salwani (Archives of The Medicine and Case Reports, 2026)
Sodium-glucose cotransporter-2 inhibitors (SGLT2i) have revolutionized the management of diabetic kidney disease (DKD), offering profound renoprotection through the restoration of tubuloglomerular feedback and reduction of intraglomerular pressure. However, their perioperative safety profile remains a subject of intense debate. While the pharmacological mechanisms of SGLT2 inhibitors may theoretically ameliorate ischemia-reperfusion injury and prevent acute kidney injury (AKI), the metabolic shift towards ketogenesis raises concerns regarding perioperative Euglycemic Diabetic Ketoacidosis (euDKA). This meta-analysis aimed to quantify the risks of AKI and euDKA in DKD patients continuing or withholding SGLT2i prior to non-cardiac surgery. A systematic review and meta-analysis were conducted following PRISMA 2020 guidelines. We analyzed data from seven high-quality studies, including large-scale propensity-matched cohorts and randomized controlled trials published through 2026, involving patients with type 2 diabetes mellitus (T2DM) and DKD undergoing non-cardiac surgery. The primary outcomes were the incidence of postoperative AKI (KDIGO criteria) and euDKA. Secondary outcomes included 30-day mortality and urinary tract infections. Pooled Odds Ratios (OR) with 95% Confidence Intervals (CI) were calculated using a random-effects model (DerSimonian-Laird). The pooled analysis included a total of 142,530 patients. The use of SGLT2 inhibitors was associated with a robust and statistically significant reduction in postoperative AKI compared to non-users (Pooled OR 0.69; 95% CI 0.62–0.78; p < 0.001). This renoprotective signal was consistent across various surgical subtypes. Conversely, SGLT2i use was associated with an increased risk of euDKA (Pooled OR 2.34; 95% CI 1.45–3.78; p = 0.001), although the absolute event rate remained low (<1%). Subgroup analysis revealed that preoperative withdrawal of <24 hours significantly exacerbated DKA risk compared to a withdrawal period of 3–4 days, without providing additional protection against AKI. In conclusion, in patients with DKD undergoing non-cardiac surgery, preoperative SGLT2 inhibitor use presents a distinct renoprotective paradox: it significantly reduces the risk of AKI, likely through attenuation of oxidative stress and preservation of renal oxygenation, but increases the risk of euDKA. The benefits of AKI prevention outweigh the rare risk of DKA, provided a structured preoperative withdrawal protocol of 3 days is strictly implemented.